The Effect of Rough Surface Statistics on Diffuse Scattering at Terahertz Frequencies - Alissa, Mai; Kreul, Theo; Kaiser, Thomas (2019 European Conference on Networks and Communications, EuCNC 2019, 2019)
In Terahertz region, the diffuse scattering phenomenon by rough surfaces has a remarkable effect of non-line of sight (NLOS) channel propagation. Several parameters contribute to form a specific distribution of the scattered rays, and the angular distribution of the scattered field varies depending on the surface roughness parameters. Yet, a clear understanding of how these parameters adjust the scattered field distribution is still missing. In this work, we investigate the scattering properties of indoor materials at Terahertz band. This is done via full-wave simulation of the diffused scattering by rough samples varies in their roughness characteristics. Then, the role of each statistical parameter is investigated separately. It was proven that both the surface correlation function and the correlation length have an influence on the far field scattered energy. While the height standard deviation has a direct effect on the specular part, the correlation length seems to affect the power distribution out of the specular direction. The longer the correlation length, the more energy is accumulated closer to the specular direction. The resulting angular distribution can be then applied for obtaining more accurate NLOS channel predictions.
Created from Fastlane, Scopus look-up
Keywords: indoor scattering model; rough surfaces; surface correlation.; terahertz communications